Skewly replicating hot data to construct a power-efficient storage cluster. (April 2015) - Zhang, Lingwei; Deng, Yuhui; Zhu, Weiheng; Zhou, Jipeng; Wang, Frank
Abstract: The exponential data growth is presenting challenges to traditional storage systems. Component-based cluster storage systems, due to their high scalability, are becoming the architecture of next generation storage systems. Cluster storage systems often use data replication to ensure high availability, fault tolerance, and load balance. However, this kind of data replication not only consumes a large amount of storage resources, but also generates more energy consumption. This paper presents a power-aware data replication strategy by leveraging data access behavior. This strategy uses 80/20 rule (80% of the data accesses often go to 20% of the storage space) to skewly replicate only a small amount of frequently accessed data. Furthermore, the storage nodes are divided into a hot node set and a cold node set. Hot nodes, which store a small amount of hot data copies, are always in an active state to guarantee the QoS of the system. The cold nodes which store a large volume of infrequently accessed cold data are placed in a low-power state, thus reducing the energy consumption of the cluster storage system. Simulation results show that the proposed strategy can effectively reduce the resource and energy consumption of the system, while ensuring system performance.